A new Eugenia (Myrtaceae) from Suriname with ‘six petals’ display - Giaretta, Augusto; Sano, Paulo Takeo (Phytotaxa, 2020)
Eugenia has ca. 1,100 species mostly with Neotropical distribution. Morphological circumscription of Eugenia has substantially changed over the last 10 years. Recent studies based on molecular and morphological data support a broad morphological circumscription of Eugenia including species with calyx fused and displaying apparently six petals. This is the case of a species here newly described. A detailed description, illustration, conservation assessment and a distribution map are provided.